THE IMPACT OF TRUST FACTORS IN IT-BASED PLATFORMS ON ACADEMIC PUBLISHING INTENTIONS IN UNIVERSITY WAQF INSTITUTIONS: STRENGTHENED BY RELIGIOUS AND SOCIOECONOMIC VALUES OF WAQF - Machfud, Syafrina; Mawardi, Imron; Bonang, Dahlia (JURNAL MANAJEMEN DAKWAH, 2025)
This study investigates the formation of trust within an Information Technology (IT)-based digital environment and its influence on beliefs, intentions, and behaviors related to academic publishing through University Intellectual Property Waqf Institutions (UIPWI) utilizing Open Access (OA) digital platforms. The research integrates and extends the Theory of Planned Behavior (TPB), Theory of Reasoned Action (TRA), Self-Determination Theory (SDT), Technology Acceptance Model (TAM), and the Theory of Open Access in a quantitative survey design. The sample includes students from Airlangga University and various public and private universities across Indonesia. Data were collected online via WhatsApp group invitations using Google Forms and analyzed with Partial Least Squares Structural Equation Modelling (PLS-SEM). The findings reveal that technological, individual, and social trust determinants positively affect waqif trust in UIPWI operating on OA platforms. Moreover, religious beliefs strengthen the relationship between trust determinants and the intention to publish academic works through UIPWI via gold or green access schemes. This study provides strategic insights for universities planning to establish UIPWI and for stakeholders such as government agencies and the Indonesian Waqf Board (BWI). It also contributes to expanding discourse on the role of credible digital environments in fostering academic publishing through Islamic philanthropic mechanisms. A limitation of this study lies in its relatively small sample size; thus, future research is encouraged to involve larger samples and broader institutional participation to enhance the global generalizability of the findings.